On Some k-Oresme Polynomials with Negative Indices - Serpil Halıcı; Elifcan Sayın (Communications in Advanced Mathematical Sciences)
In this study, k- Oresme polynomials with negative indices, which are the generalization of Oresme polynomials, were examined and defined. By examining the algebraic properties of recently defined polynomial sequences, some important identities were given. The matrices of negative indices k- Oresme polynomials was defined. Some sum formulas were given according to this definition.